SIRT6/RXRα/retinoic acid-related signaling contributes to intestinal stem cell homeostasis during aging and is modulated by Atractylenolide II - Yaqian Cao; Chunhui Song; Xiaoqing Sun; Zhenyu Niu; Xueni Zhang; Kerong Qi; Jiazhong Cai; Wenfeng Guo; Gang Chen; Ning Li; Yanwu Li (Chemico-Biological Interactions, 2026)

Spatiotemporal evolution of CO2 plumes in a heterogeneous Heshanggou formation reservoir, Ordos Basin, China - Zijian Wang; Xuan Tang; Tieya Jing; Wentao Zhao; Gang Zhao; Xiaoming Li; Tianyi Niu; Ziheng Guan (Journal of Asian Earth Sciences, 2026)

A smartphone-integrated isothermal amplification-based point-of-care testing platform for ultrasensitive detection of severe fever with thrombocytopenia syndrome virus - Wen Li; Youqian Chen; Yuxin Niu; Yihui Yang; Tao Chen; Qin Ning; Liping Huang; Wenjun Hu; Gang Logan Liu (Analytica Chimica Acta, 2026)

Beyond pathogens: Emerging contaminant risks following the potomac sewer spill in the United States - Xiaopei Li; Qing Feng; Zhenheng Long; Kunyu Guo; Bin Liu; Peng Gao; Shan Niu; Gang Yu (Journal of Environmental Sciences, 2026)

Mulching with orchard pruning branches exerts positive effects on improving the soil micro-ecological environment and enhancing fruit quality - Minghui Ji; Longfei Li; Jintao Xu; Lijuan Gao; Huan Liu; Yue Yao; Gang Niu; Liyuan Zhang; Baofeng Hao (Plant and Soil, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Pulsed vacuum drying remodels the texture of dried jujube by regulating low-methylesterified pectin and Ca2+-mediated egg-box structures - Xiao-Xiao Niu; Ming-Qiang Xu; Jozef Mravec; Wei-Peng Zhang; Li-Zhen Deng; Guo-gang Chen; Wei-qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Genomic and functional characterization of a novel urease-producing bacterium Sulfitobacter sp. IGS-18 for simultaneous coal dust suppression and ammonia nitrogen removal during microbially induced calcite precipitation - Wen Nie; Ruoxi Li; Yue Zhao; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Alveolar macrophage–neutrophil crosstalk in acute lung injury: mechanisms, feedback loops, and therapeutic opportunities - Zi-Ai Tao; Lu-Lu Li; Jing Wang; Chun-Yu Niu; Zi-Gang Zhao (Inflammation Research, 2026)

AI weather prediction toward multi-scale earth system prediction: status and pathways - Jinglin Zhang; Qinghui Chen; Feng Zhang; Zeyi Niu; Zekai Zhang; Fenghua Ling; Bin Guo; Hailong Liu; Cong Bai; Gang Li; Renhe Zhang (Science Bulletin, 2026)

Coupling MICP with hydroxypropyl trimethyl ammonium chloride chitosan-loaded zeolite for cleaner dust consolidation: Enhanced mineralization and ammonium mitigation mechanisms - Ruoxi Li; Wen Nie; Linlin Zhang; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi (Process Safety and Environmental Protection, 2026)

Synergistic effects of cationic trimeric fracturing fluids on gas-coal wettability modulation and pore structure remodeling: Experimental and molecular dynamics investigations - Gang Zhou; Kai Huang; Lianjie Zhu; Haiming Yu; He Yang; Gang Li; Qunzhi Meng; Chenxi Niu; Qi Wang (Environmental Research, 2026)

Correction: Liang et al. Integration of Biofloc and Ozone Nanobubbles for Enhanced Pathogen Control in Prenursery of Pacific White Shrimp (Penaeus vannamei). Fishes 2025, 10, 218 - Qinlang Liang; Yazhi Luan; Zhengwen Wang; Jiangbo Niu; Yasong Li; Hua Tang; Zengting Li; Songming Zhu; Gang Liu (Fishes, 2026)
Songming Zhu was not included as an author in the original publication [...]

Ultrasonic-assisted acidification of sepiolite fibers towards highly stable paraffin-based phase change composites with enhanced thermal energy storage performance - Haizhen Li; Mengqian Qi; Wensheng Yang; Jiateng Hu; Mengjiao Niu; Yongshuai Xie; Tianliang Wang; Gang Yu (Applied Clay Science, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Volatile methyl siloxanes in electric vehicle cabin air: The first investigation of occurrence, influencing factors, and inhalation risks - Yujiao An; Yue Li; Xiaoliang Li; Zhendong Zhang; Jian Tang; Yu Ma; Kunyu Guo; Jianjie Chen; Shan Niu; Bin Liu; Chunzhao Chen; Gang Yu (Journal of Hazardous Materials, 2026)

Functional polymer micelles based on quaternized polyethyleneimine for efficient delivery of insoluble fungicide with synergistic antimicrobial activity - Xiaohan Meng; Junfan Niu; Qing Guo; Gang Tang; Gaohua Hu; Weiyao Yan; Xiaohong Zhang; Yuqi Huang; Jianhua Xiao; Yongqian Liang; Ruyue Han; Guangyao Yan; et al. (Journal of Environmental Chemical Engineering, 2026)

Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

Coordinated horizontal transfer of multiple genes assembles a carotenoid biosynthesis pathway in aphids - Rong Hu; Jun Wu; Siying Li; Peiyu Yang; Gang Wu; Changying Niu; Shuai Zhan; Yazhou Chen (Insect Biochemistry and Molecular Biology, 2026)

Chemokine CCL2 Mediates Neuroglial Crosstalk and Drives Chronic Pain Pathogenesis - Junyu Lu; Yunxin Shi; Yongkang Li; Ziyi Niu; Shengxi Wu; Ceng Luo; Rou-Gang Xie (Neuroscience Bulletin, 2025)

Domain Adaptation with Deep Feature Clustering for Pseudo-Label Denoising in Heterogeneous SAR Image Classification - Sheng-Jie Luo; Zhi-Gang Liu; Xi-Hai Li; Yi-Ting Wang; Xiao-Niu Zeng; Zhi-Hao Zheng; Heng Li (Applied Geophysics, 2025)

Amphiphilic block copolymer-based fire suppression material – Study on coal spontaneous combustion prevention and extinguishing performance - Gang Zhou; Hongrui Qu; Bo Wei; Tianrui Niu; Yongmei Wang; Xiaosu Dong; Rulin Liu; Lin Li; Shuailong Li (Journal of Environmental Chemical Engineering, 2025)

Coupling crop growth models and machine learning for scalable winter wheat yield estimation across major wheat regions in China - Jiyuan Xie; Dongyan Zhang; Ning Jin; Tao Cheng; Gang Zhao; Dong Han; Zhen Niu; Weifeng Li (Agricultural and Forest Meteorology, 2025)

Immunogenicity assessment of a swine fever-swine circovirus type 2 duplex vaccine candidate created using the Zera nanoparticle delivery method - Pu Wang; Gang Zhang; Qiang Liu; Lingling Jiang; XiaoXia Niu; Min Fang; Weifeng Gao; Yulong He; Yong Li; Jianhong Shu; Sinong Zhang (Veterinary Immunology and Immunopathology, 2025)

Numerical simulation of seismic waves in transversely isotropic media based on orthogonal body-fitted grids - Zhi-qiang Liu; Gang-zhu Li; Lei Huang; Xing-guo Niu; Xiao-meng Zhang; Cheng Gao (Applied Geophysics, 2025)

Integration of Biofloc and Ozone Nanobubbles for Enhanced Pathogen Control in Prenursery of Pacific White Shrimp (Penaeus vannamei) - Qinlang Liang; Yazhi Luan; Zhengwen Wang; Jiangbo Niu; Yasong Li; Hua Tang; Zengting Li; Songming Zhu; Gang Liu (Fishes, 2025)
This study investigates the synergistic effects of integrating ozone nanobubbles (generated via a pure oxygen-fed reactor with nanobubble-diffusing air stones) and biofloc technology (BFT) on water quality optimization, pathogenic load reduction, and growth performance enhancement in Pacific white shrimp (Penaeus vannamei) prenursery aquaculture systems. Four treatments were tested: a clear water control (CW), ozonated clear water (CW + O), biofloc (FLOC), and biofloc with ozone (FLOC + O). The FLOC + O group significantly improved water quality, reducing total ammonia nitrogen (TAN) by 61%, nitrite nitrogen (NO2−-N) by 78% compared to CW, and total suspended solids (TSS) by 21% compared to FLOC (p = 0.0015). Ozone application (maintained above 0.3 mg/L, 15 min/day) demonstrated robust pathogen suppression, achieving a sharp reduction in Muscle Necrosis Virus (MNV), a 99.5% inhibition of Vibrio spp. (from 228,885 to 107 CFU/mL), and the clearance of Epistylis spp., as determined via optical microscope. These enhancements directly translated to superior biological outcomes, with the FLOC + O group exhibiting an 82% survival rate (vs. 40% in CW) and 13% higher final body weight (11.65 mg vs. 10.32 mg in CW). The integration of ozone and BFT also accelerated larval development and improved the Zoea II to Mysis I metamorphosis success rate. By maintaining stable microbial communities and reducing organic waste, the combined system lowered the water exchange frequency by 40% and eliminated the need for prophylactic antibiotics. These results demonstrate that ozone–BFT integration effectively addresses key challenges in shrimp prenursery—enhancing disease resistance, optimizing water conditions, and improving growth efficiency. The technology offers a sustainable strategy for the intensive prenursery of Pacific white shrimp, balancing ecological resilience with production scalability.

The important role of TLR2/MyD88/JNK in regulating the pathogenesis and inflammation induced by pseudorabies virus in mice - Jingyi Niu; Gang Li; Yiyu Liu; Chao Wan; Yixuan Li; Yu Dai; Haixia Hu; Lianci Peng; Rendong Fang; Chao Ye (Veterinary Microbiology, 2025)

Preparation of environment-friendly gel-protein foam and its fire suppression performance for lithium-ion batteries - Gang Zhou; Yuying Li; Yang Liu; Yang Kong; Viet Doan Dao; Shuai Yuan; Qunzhi Meng; Chenxi Niu; Zonglei Mou; Siqi Yang; Qi Zhang (Fuel, 2025)

Effects of Cadmium and Lead Co-exposure on Sleep Status in Rural Areas Northwestern China - Min Huang; Honglong Zhang; Haiping Wang; Jingping Niu; Bin Luo; Gang Wu; Xun Li; Jun Yan (Biological Trace Element Research, 2025)

Humidity controls soil organic carbon accrual in grassland on the Qinghai–Tibet Plateau - Zhen-Huan Guan; Bin Jia; Zi-qi Niu; Xiao-Ming Mou; Jie Chen; Fen-Can Li; Yi-Ning Wu; Shijie Ning; Kuzyakov Yakov; Xiao Gang Li (Soil Biology and Biochemistry, 2025)

Targeted isolation of lignans from the roots of Anthriscus sylvestris (L.) Hoffm. by small molecule accurate recognition technology - Yan-ling Liu; Yan-gang Cao; Ya-juan Zheng; Ying Niu; Lan Chen; Xu Chen; Xin-yi Ma; Xiang-da Li; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Boosting charge separation and active sites exposure by hollow S-scheme MoSe2/Fe2O3 heterojunction for enhanced photocatalytic peroxymonosulfate activation towards ciprofloxacin removal - Lu Li; Cheng-Gang Niu; Hai Guo; Ya-Ya Yang; Hui-Yun Liu; Ming Yan (Chemical Engineering Journal, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Cu inanchored MnO/carbonaceous frameworks trigger peroxymonosulfate activation for enrofloxacin degradation: ROS generation and pollutant attacking processes - Huai-Yuan Niu; Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Wen-Jie Yang; Ming Yan; Cheng-Gang Niu; Ji-Shan Li (Journal of Environmental Chemical Engineering, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Experimental and numerical investigation on energy-saving performance of radiative cooling coating for metal container office - Qingdong Xuan; Jiancong Lao; Bin Zhao; Guiqiang Li; Gang Pei; Jianlei Niu; Jian-Guo Dai (Energy and Buildings, 2024)

Study on the mechanism and stability of microbially induced struvite precipitation (MISP) for enhanced immobilization of uranium - Yao-ting Duan; Xin Xu; Lei Niu; Zhe Wang; Xiao-gang Huang; Chun-li Zheng (Journal of Cleaner Production, 2024)

Biological activities and mass fragmentation pathways of meroterpenoid cochlioquinones from plant pathogenic fungus Bipolaris sorokiniana - Qi Li; Jian-zi Liu; Jian Yang; Yan-duo Wang; Sheng-Xiang Yang; Shu-bin Niu; Gang Ding (Food Chemistry, 2024)

αExtractor: a system for automatic extraction of chemical information from biomedical literature - Jiacheng Xiong; Xiaohong Liu; Zhaojun Li; Hongzhong Xiao; Guangchao Wang; Zhenjiang Niu; Chaoyuan Fei; Feisheng Zhong; Gang Wang; Wei Zhang; Zunyun Fu; Zhiguo Liu; et al. (Science China Life Sciences, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

A novelty evaluation of the impact of digitalization on energy internet value creation - Jin Zhang; Wenjia Zhang; Jinkai Li; Tong Niu; Shoulin Liu; Gang Lu; Zhe Liu; Xiaochen Wang (Environment, Development and Sustainability, 2023)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

Preparation, properties and applications of porous hydrogels containing thiol groups for heavy metal removal - Huai-Yuan Niu; Jin-Cheng Li; Ji-Shan Li; Cong Yi; Cheng-Gang Niu (Journal of Environmental Chemical Engineering, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

Unravelling the role of reactive oxygen species in ultrathin Z-scheme heterojunction with surface zinc vacancies for photocatalytic H2O2 generation and CTC degradation - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Chao Liang; Hai Guo; Ya-Ya Yang; Lu Li (Chemical Engineering Journal, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Combined analysis of potential distribution prediction and phenotypic data of Polygonatum sibiricum in China - Xinfei Zhang; Gang Li; Peng Gao; Guanghui Jiang; Qian Zhao; Junfeng Niu; Donghao Wang; Shiqiang Wang; Zhezhi Wang (Plant Ecology, 2023)

Prediction of potentially suitable distribution areas of Thesium chinense Turcz. in China against the background of climate change - Peng Gao; He Si; Qian Zhao; Gang Li; Xinfei Zhang; Minghao Guo; Shiqiang Wang; Junfeng Niu; Zhezhi Wang (Plant Ecology, 2023)

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Synergy between sulfur vacancy and Schottky junction into CoB/ZnIn2S4–S photocatalysts: Oriented charge flow and regulated carriers transfer dynamics to activate reactive oxygen species generation for efficient photocatalytic disinfection - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Meng-Ke Li; Ya-Ya Yang; Ning Tang; Lu Li; Lei Zhang (Journal of Cleaner Production, 2023)

Fir sawdust as a low-cost and easily recyclable adsorbent: efficient removal of Pb(II), Cu(II), and Zn(II) contaminants from wastewater - Gang Zhou; Shuailong Li; Chenxi Niu; Qi Wang; Xinyuan Zhang; Qunzhi Meng; Lin Li (Environmental Science and Pollution Research, 2023)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Dynamic Penetration Process of Torpedo Anchors into Sand Foundation - Gang Li; Jinli Zhang; Jinglin Niu; Jia Liu; Yiran Yang (Journal of Marine Science and Engineering, 2022)
Torpedo anchors are a new type of anchoring system in deepwater that is much more economical than conventional anchoring methods. The dynamic penetration process is vitally important to the installation of torpedo anchors. Based on the spherical cavity expansion theory, the dynamic response characteristics of pressure-locked soils are analyzed using the Mohr-Coulomb criterion. The equations for the penetration of torpedo anchors with bullet-shaped heads are established considering rod friction. Subsequently, the analytical solutions for velocity, acceleration, and final penetration depth and the approximate analytical solution for penetration depth vs. time are obtained. The established penetration equation is solved using MATLAB software to obtain a semi-analytical solution, and the model tests on the penetration of a torpedo anchor with different initial velocities into saturated sand with different densities were conducted. A comparison of the test results shows that the analytical solution and the semi-analytical solution can well predict the model test results, indicating that the established analytical method can be used to analyze the penetration process of torpedo anchors. The research results can provide a guideline to the installation of torpedo anchors into the seabed in actual engineering.

Prognostic implication and immunotherapy response prediction of a costimulatory molecule signature in kidney renal clear cell carcinoma - Gaoteng Lin; Yuanyuan Yang; Qingfu Feng; Fangfang Zhan; Chuangxin Sun; Yuanjie Niu; Gang Li (Immunogenetics, 2022)

Circular RNA circ_0124644 exacerbates the ox-LDL-induced endothelial injury in human vascular endothelial cells through regulating PAPP-A by acting as a sponge of miR-149-5p - Gang Wang; Yu Li; Zhenbin Liu; Xiuna Ma; Menghu Li; Qingwei Lu; Yanfang Li; Zengzhen Lu; Li Niu; Zixuan Fan; Zhangcheng Lei (Molecular and Cellular Biochemistry, 2020)

Evoked-potential audiogram variability in a group of wild Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhi-Tao Wang; Jiao Li; Peng-Xiang Duan; Zhi-Gang Mei; Fu-Qiang Niu; Tomonari Akamatsu; Pei-Yu Lei; Lu Zhou; Jing Yuan; Yu-Wei Chen; Alexander Ya Supin; Ding Wang; et al. (Journal of Comparative Physiology A, 2020)

RNAi of the nuclear receptor HR3 suggests a role in the molting process of the spider mite Panonychus citri - Gang Li; Xun-Yan Liu; Xi Han; Jin-zhi Niu; Jin-Jun Wang (Experimental and Applied Acarology, 2020)

Expression dynamics of key ecdysteroid and juvenile hormone biosynthesis genes imply a coordinated regulation pattern in the molting process of a spider mite, Tetranychus urticae - Gang Li; Qin-Zhe Sun; Xun-Yan Liu; Jun Zhang; Wei Dou; Jin-Zhi Niu; Jin-Jun Wang (Experimental and Applied Acarology, 2019)

Well-balanced central WENO schemes for the sediment transport model in shallow water - Shouguo Qian; Gang Li; Fengjing Shao; Qiang Niu (Computational Geosciences, 2018)

A Fluorescence Sensor for Lead (II) Ions Determination Based on Label-Free Gold Nanoparticles (GNPs)-DNAzyme Using Time-Gated Mode in Aqueous Solution - Xiao-Yu Wang; Cheng-Gang Niu; Li-Juan Guo; Liu-Yin Hu; Sheng-Quan Wu; Guang-Ming Zeng; Fei Li (Journal of Fluorescence, 2017)

Ten polymorphic microsatellite markers characterized for Schizothorax pseudaksaiensis and applied for population genetic analysis - MING MING BAO; QIONG ZHOU; CONG XIN XIE; LIN GANG CAI; JIAN GONG NIU; HONG LI (Journal of Genetics, 2016)

DTC-GO as Effective Adsorbent for the Removal of Cu2+ and Cd2+ from Aqueous Solution - Li-Juan Guo; Cheng-Gang Niu; Xiao-Yu Wang; Xiao-Ju Wen; Guang-Ming Zeng (Water, Air, & Soil Pollution, 2016)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Deep-Red Phosphorescent Iridium(III) Complexes Containing 1-(Benzo[b] Thiophen-2-yl) Isoquinoline Ligand: Synthesis, Photophysical and Electrochemical Properties and DFT Calculations - Gao-Nan Li; Ying Zou; Yi-Ding Yang; Jiao Liang; Feng Cui; Tao Zheng; Hui Xie; Zhi-Gang Niu (Journal of Fluorescence, 2014)

Detection of three pear viruses by multiplex RT-PCR assays with co-amplification of an internal control - Bing-Gang Ma; Jian-Xin Niu; M. Morley-Bunker; Li-Zhong Pan; Hu-Ping Zhang; Lu-Xia Zhang (Australasian Plant Pathology, 2008)

Identification and Characterization of sanH and sanI Involved in the Hydroxylation of Pyridyl Residue During Nikkomycin Biosynthesis in Streptomyces ansochromogenes - Zhoujie Xie; Guoqing Niu; Rui Li; Gang Liu; Huarong Tan (Current Microbiology, 2007)